Checks and Balances: The Concept and Its Implications for Corruption - Luciano Da Ros; Matthew M. Taylor (Revista Direito GV)
Abstract It is often assumed that checks and balances are effective in curbing corruption, in part because checks and balances are so often assumed to be synonymous with the separation of powers. We argue that checks and balances are only one of several potential manifestations of the separation of powers. We suggest that the apparent correlation between checks and balances and control of corruption is driven by a variety of conditions antecedent to both. Using examples from Western democracies, we demonstrate that the concept of checks and balances is by itself an empty vessel, made effective only by “hard” factors such as the balance of political forces and “soft” factors such as the adherence of elites to particular behavioral norms. This does not mean that checks and balances cannot be useful, but rather that our assumptions about their precise utility may be misinformed: the relationship between checks and balances and curbing corruption is at best indirect.